Ivan the Terrible: first Tsar of Russia - De Madariaga, Isabel (Yale University Press, 2006)
Inhalt: The historical background -- The reign of Vasily III -- Ivan's birth, childhood, adolescence, coronation and marriage -- The era of Aleksei Adashev -- The 'government of compromise' -- The conquest of Kazan' -- The dynastic crisis of 1553: domestic and military policy, and the arrival of the English -- The war in Livonia and the end of the 'chosen council' -- The death of Anastasia, and Ivan's second marriage -- Tsar Ivan and Prince Andrei Kurbsky -- The setting up of the Oprichnina -- War in Livonia and the Zemskii Sobor of 1566 -- The Boyar plot: 1) the letters to King Sigismund -- The Boyar plot: 2) the executions of Ivan Fedorov, Metropolitan Filipp and Vladimir of Staritsa -- Armageddon -- Foreign policy and the tatar invasions -- The end of the Oprichnina, and the succession to the Polish-Lithuanian crown -- Grand Prince Simeon Bekbulatovich -- Peace negotiations -- The truce of Iam Zapol'sky -- The death of Ivan -- Ivan's legacy to Russia